Anaerobic peritonitis caused by Clostridium septicum as a complication of routine castration in a 2‐year‐old Warmblood horse. (12th October 2015) - Shearer, T. R.; Smith, A. D.; Freeman, D. E.; Regan, S. A.
Summary: This case report describes an unusual case of anaerobic peritonitis in a 2‐year‐old horse following castration. The horse was evaluated 2 weeks following castration for signs of acute, severe abdominal pain and swelling surrounding a previous castration site. Physical examination revealed marked scrotal and ventral abdominal oedema that was cool and crepitant upon palpation. Ultrasonographic evaluation was unrewarding because gas shadowing distributed throughout the subcutis prevented imaging of the abdominal cavity. Ventral midline celiotomy revealed a copious amount of malodorous, serosangious, cloudy peritoneal fluid that was submitted for culture. Abdominal exploration revealed the gastrointestinal tract to be in its anatomically correct position. There was diffuse petechiation of the small intestine and large intestine, oedema and crepitant swelling surrounding the left inguinal ring and body wall. The abdomen was lavaged with 10 l of sterile saline prior to closure of the celiotomy and the left castration incision was opened digitally, releasing a large volume of serosanguinous fluid and gas that flowed freely from the incision site and deeper inguinal tissues. The horse was placed in the recovery box where it suffered cardiac arrest. Culture of the peritoneal fluid revealed heavy growth of Clostridium septicum . This case of anaerobic peritonitis represents an unusual complication following castration not previously reported in the horse.